Reforestation after fires of different intensity in pine forests of Central Siberia - S. V. Zhila; G. A. Ivanova; V. A. Ivanov; P. A. Tsvetkov (Сибирский лесной журнал, 2019)
Every year in Siberia, there are thousands of forest fires that damage forests on huge areas. The main part of fires occurs in pine forests. In this regard, the paper discusses the features of postfire regeneration in pine forest, depending on the fire intensity and the time after the fire. The dynamics of the number, growth and viability of natural regeneration of pine after fires in the pine forests of the southern and middle taiga were evaluated. The dependence of the number of young growth of the duration of the period after the fire exposure, which is particularly marked after highintensity fire, a correlation coefficient of 0.81. A close relationship between the amount of undergrowth and the intensity of fire, the correlation coefficient 0.82. In the pine forest after fires of renewal takes place without a shift in the species with satisfactory performance. After lowintensity fires, the formation of lifecapable undergrowth in pine forests extends for a longer period. It is established that at the initial stage of postfire succession the accumulation of phytomass of natural regeneration in pine forests is also determined by the intensity of the fire and the time after the fire.